1987
DOI: 10.1007/bf00296249
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of methionine uptake by methotrexate in mouse leukemia L1210 cells

Abstract: Methionine-auxotrophic L1210 cells were used to study the effect of methotrexate (MTX) on methionine uptake and metabolism. MTX was shown to inhibit amino acid transport systems and cause a decrease of methionine uptake into L1210 cells. Conversely, a nonmetabolizable amino acid analogue reduced MTX uptake into L1210 cells. MTX also blocked the transfer of the beta carbon from serine into methionine. Therefore, methionine deprivation may be an additional mechanism of action for MTX in methionine-auxotrophic tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…We have previously shown that a L1210 mouse leukemia cell line resistant to methotrexate (L121OMTX) exhibits a 3-fold increase in DHFR (5). This increase in resistance to cisplatin with EC50 values of 2.0 and 3.6 ,uM for L1210S and L121OMTX cells, respectively ( cisplatin (3-fold as here demonstrated) seems to involve the thymidylate synthase cycle.…”
Section: And Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We have previously shown that a L1210 mouse leukemia cell line resistant to methotrexate (L121OMTX) exhibits a 3-fold increase in DHFR (5). This increase in resistance to cisplatin with EC50 values of 2.0 and 3.6 ,uM for L1210S and L121OMTX cells, respectively ( cisplatin (3-fold as here demonstrated) seems to involve the thymidylate synthase cycle.…”
Section: And Discussionsupporting
confidence: 70%
“…The notion linking cisplatin to the thymidylate synthase cycle began with reports that cisplatin interacts at the membrane (5,7,(17)(18)(19). For instance, cisplatin, MTX, and other folate antagonists have all been shown to alter transport of neutral amino acids (and, in particular, methionine) across the membrane (5,7,(17)(18)(19)(20)(21).…”
Section: And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dTMP Synthase Assay. dTMP synthase activity was measured in extracts of A2780 cells by the amount of tritium released to H2O from [5-3H]dUMP as described (13), except that 1% Triton X-100 was included in the buffer to extract the cells.…”
mentioning
confidence: 99%
“…If the activity of this enzyme, as measured in vitro, reflects the activity in vivo, then an increased flux of one-carbon units through this step into the folate pathway in monkeys may lead to an accumulation of hepatic HCOH4folate at the expense of H4folate. The results of studies of cultured mammalian cells suggest that the activity of serine hydroxyrmethyltransferase is directly related to the incorporation of the serine carbon-3 into DNA via folate-dependent reactions (36,37).…”
Section: Discussionmentioning
confidence: 99%